Technique for designing and optimization of the Francis turbine blade system - M. Omran; A. A. Zharkovskiy; V. A. Schur; D. G. Svoboda (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A technique for designing the blade systems of Francis turbine is proposed. Starting with the determination the main parameters of the turbine components, where it is compatible with the operation of a hydraulic turbine at a given head. Also, the diameter of the impeller required to generate the nominal power. Then, using the realizing of the quasi-three-dimensional approach, the shape of the blade is obtained as a first approximation for a given blade, a series of calculations of three-dimensional single-phase and twophase viscous flow is performed to determine the efficiency of the turbine at different operating modes, the cavitation properties of the turbine, respectively. The critical cavitation coefficient is determined for three operating points of hydraulic turbines. Using Multi-objective Genetic Algorithm (MOGA), the optimization of energy and cavitation properties is carried out for three operations pointes. The mathematical model is based on the Latin hypercube method. As a result of the optimization, a significant improvement in the efficiency of the hydraulic turbine has been obtained, especially at partial loads.